2020
DOI: 10.1115/1.4046878
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fin Parameters to Reduce Entropy Generation and Melting Time of a Latent Heat Storage Unit

Abstract: One of the challenges in the design and development of a latent heat storage unit (LHSU) is to increase the charging and discharging rates which are inherently low because of low thermal conductivity of phase change materials (PCM). Out of various heat transfer enhancement techniques, employing annular fins is very simple, efficient and no fabrication complexity is involved. Fin parameters (fin size and number of fins) significantly influence the enhancement in heat transfer rate. Hence, optimization of fin pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The thermal energy stored/released during the phase change process is latent heat. In recent years, thermal energy storage using phase change materials has been a major topic of research, due to its large energy density and nearly isothermal heat transfer process [6,7]. Based on the phase change process, phase change materials (PCMs) can be categorized into solid-solid, solid-liquid, solid-gas, and liquid-gas.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal energy stored/released during the phase change process is latent heat. In recent years, thermal energy storage using phase change materials has been a major topic of research, due to its large energy density and nearly isothermal heat transfer process [6,7]. Based on the phase change process, phase change materials (PCMs) can be categorized into solid-solid, solid-liquid, solid-gas, and liquid-gas.…”
Section: Introductionmentioning
confidence: 99%
“…Kalapala and Devanuri 1 on reviewing several research works concluded that the optimized ratio of shell to tube diameter should be nearly 4. Kaplala and Devanuri 13 gave the nondimensional correlation for fin spacing and fin diameter by optimizing the melting time for radial finned LHTES HX. In the present study same pitch and diameter of fins are considered for radial and spiral finned LHTES HX.…”
Section: Problem Description and Modelingmentioning
confidence: 99%
“…The radius of the radial fins is considered from the nondimensional parameters given by Kalapala and Devanuri. 13 The same diameter is considered for spiral fins. The radial distance of longitudinal fins is considered to be equal to the radius of radial fins.…”
Section: Problem Description and Modelingmentioning
confidence: 99%
See 2 more Smart Citations